Measuring the Effectiveness of Public Organizational Information System Functions - Usman; Piji Pakarti; Entot Suhartono (Institute of Computer Science (IOCS), 2021)
This study aims to identify validated constructs and their attributes that are used to assess the effectiveness of the public organization's information system functions. In this study, the function of information systems can be in the form of work units, groups of people, or individuals, who are given responsibility for an organization's information system. This study uses literature studies and in-depth interviews with individuals who are responsible for the development, management and operation of information systems in 5 public organizations in Semarang City, to identify 98 items measuring the effectiveness of information system functions. A total of 192 sample items were obtained from a survey of end users of information systems in 5 public organizations in Semarang City. Using principal component analysis and second-order confirmatory factor analysis methods, this study has succeeded in validating 4 main dimensions, namely: Institutional (3 factors), Service Quality (3 factors), System Quality (4 factors), and Individual and Organizational Benefits ( 4 factors). The final instrument can be used to evaluate the effectiveness of existing information system functions, and the results obtained can be used to determine the initial status of effectiveness and for benchmarking.